2010
DOI: 10.1002/cncr.25542
|View full text |Cite
|
Sign up to set email alerts
|

The association of race/ethnicity, insurance status, and socioeconomic factors with breast cancer care

Abstract: BACKGROUND: Few data are available on how race/ethnicity, insurance, and socioeconomic status (SES) interrelate to influence breast cancer treatment. The authors examined care for a national cohort of breast cancer patients to assess whether insurance and SES were associated with racial/ethnic differences in care. METHODS: The authors used multivariate logistic regression to assess the probability of definitive locoregional therapy, hormone receptor testing, and adjuvant systemic therapy among 662,117 white, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
146
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(159 citation statements)
references
References 30 publications
11
146
2
Order By: Relevance
“…This may be because of the relatively small numbers of patients in the treatment-eligible subgroups or because of our focus on a single geographic area. Nevertheless, many other studies have documented persistent disparities in treatment receipt, [30][31][32][33][34][35][36][37][38] and understanding how differences in knowledge may affect disparities among larger and broader cohorts is essential. We did observe differences in treatment by stage and age, consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because of the relatively small numbers of patients in the treatment-eligible subgroups or because of our focus on a single geographic area. Nevertheless, many other studies have documented persistent disparities in treatment receipt, [30][31][32][33][34][35][36][37][38] and understanding how differences in knowledge may affect disparities among larger and broader cohorts is essential. We did observe differences in treatment by stage and age, consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…As introduced earlier, a limited number of studies have explored racial/ ethnic differences in the use of adjuvant hormonal therapies for the treatment of hormone receptor-positive breast cancer. 5,9,10,16,17 Unlike our analysis, prior studies have compared use of adjuvant hormonal therapy among racial/ethnic groups using non-Hispanic white women as the referent category, making direct comparisons with our study difficult. Similar to our study, however, three of the prior studies documented that African American women had the lowest frequency of adjuvant hormonal therapy use.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, however, three of the prior studies documented that African American women had the lowest frequency of adjuvant hormonal therapy use. 5,9,17 Specifically, two of these studies 5,17 reported that non-Hispanic white women were more likely to use adjuvant hormonal therapy than African American women (OR 4.59 and OR = 2.09, respectively), and the third study 9 reported a lower likelihood of adjuvant hormonal therapy use among both African American and Hispanic women compared to non-Hispanic white women (OR 0.91 and OR 0.95, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations